2021
DOI: 10.3389/fmed.2021.748144
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Brain Abscess From Cystic Glioma Using Conventional MRI Based on Deep Transfer Learning Features and Hand-Crafted Radiomics Features

Abstract: Objectives: To develop and validate the model for distinguishing brain abscess from cystic glioma by combining deep transfer learning (DTL) features and hand-crafted radiomics (HCR) features in conventional T1-weighted imaging (T1WI) and T2-weighted imaging (T2WI).Methods: This single-center retrospective analysis involved 188 patients with pathologically proven brain abscess (102) or cystic glioma (86). One thousand DTL and 105 HCR features were extracted from the T1WI and T2WI of the patients. Three feature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 39 publications
0
16
0
1
Order By: Relevance
“…Their findings were promising, with models’ AUCs superior to 92% and their performances superior to those from experienced radiologists. Finally, the remaining two studies investigated the ability of radiomics to differentiate between gliomas (in particular, necrotic glioblastomas [ 60 ] and cystic gliomas [ 61 ]) and brain abscess.…”
Section: Resultsmentioning
confidence: 99%
“…Their findings were promising, with models’ AUCs superior to 92% and their performances superior to those from experienced radiologists. Finally, the remaining two studies investigated the ability of radiomics to differentiate between gliomas (in particular, necrotic glioblastomas [ 60 ] and cystic gliomas [ 61 ]) and brain abscess.…”
Section: Resultsmentioning
confidence: 99%
“…The parameters of several deep learning networks were trained by maximal rectangular slice ROIs of EGC, including Resnet152, Resnet101, Resnet50, Resnet34, Resnet18, Wide_resnet101_2, Wide_resnet50_2, and Inception v3. Then, convolution neural networks based on pre-trained TL networks were used to extract DTL features, which followed the following steps: the slices of ROIs were fed to the pre-trained network; the average probability from all slices was used to generate TL features; and the penultimate FC layer output was used as TL features ( 21 ). Based on these pre-trained deep learning networks, we extracted 512–2,048 transfer learning features, respectively ( Supplementary Table 6 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, acquiring a large number of medical images is difficult ( 20 ). Due to a pre-trained CNN known as “transfer learning (TL)” can be used to minimize overfitting with a small training size, TL has gradually been used in various medical image analysis domains in recent years ( 21 , 22 ). TL increases model performance in target tasks by transferring previously learned features from source tasks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiomics has recently emerged as a promising field of research based on the hypothesis that quantitative analysis of medical images can capture additional information that helps infer phenotypes and gene-protein signatures and provide prognostic information [ 11 , 12 ]. More recently, radiomics has been used to identify brain abscess from cystic gliomas [ 13 ], predict the molecular subtypes of HGGs (such as IDH [ 14 , 15 ] and MGMT [ 16 ] status), assess the antiangiogenic treatment response of recurrent glioblastomas (GBMs) [ 17 ], and stratify the risk of patients with GBMs [ 18 ]. Previous radiomics analysis of GBMs has shown that the radiomics signature holds better prognostic value than clinical and radiological risk models in predicting survival [ 18 ].…”
Section: Introductionmentioning
confidence: 99%